Impact of Staff Training and Development on Employee Performance: The Moderating Role of Work Engagement (Global Journal of Management and Business Research, 2021)
The Technical University Act, 2016 (Act 922) converted 9 Polytechnics to Technical University status. Yet, the quality of technical and vocation education in Ghana has come under intense scrutiny in recent years. Scholars attribute this to inability of technical universities to identify and to initiate programs to meet the training and development needs of administrators and faculty, to adequately prepare them to deliver quality performance outcomes. This paper therefore sets out to i) determine the impact of staff training and professional development on employee performance and ii) examine the moderating role of work engagement on the impact of staff training and
Keywords: staff training; professional development; work engagement; employee performance; technical universities; ghana